PENGARUH CAPITAL ADEQUACY RATIO, BOPO, LOAN TO DEPOSIT RATIO, DANA PIHAK KETIGA DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Illiyah, Illiyah; Istanti, Sri Layla Wahyu; Muniroh, Hetty (JAB (Jurnal Akuntansi & Bisnis), 2017)
Banking is a financial industry that functions to raise funds that are less productive from the public and channel them into credit to the business world. The bank functions as an intermediary institution. By using financial ratios, investors can find out the factors that affect the profitability of a bank. The measure of profitability used is Return On Assets (ROA) in the banking industry. Return On Assets (ROA) focuses the company's ability to obtain earnings in the company's operations. Some of the factors that affect bank profitability include Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), Loan to Deposit Ratio (LDR), Third Party Funds (DPK) and Non Performing Loans (NPL). This study aims to prove the effect of Capital Adequacy Ratio (CAR), Operating Costs on Operating Income (BOPO), Loan to Deposit Ratio (LDR), Third Party Funds (DPK) and Non Performing Loans (NPL) to profitability in registered banking companies on the Indonesia Stock Exchange for the period 2013-2015.The population of this research is banking companies listed on the Indonesia Stock Exchange in 2013-2015. Samples were taken using purposive sampling method. The sample in this study were 34 banking companies listed on the Indonesia Stock Exchange that fit the criteria of the study in 2013-2015. This study uses a classic assumption test consisting of multicollinearity test, autocorrelation test, heteroscedasticity test and normality test. The analytical method in this study uses multiple linear regression analysis.The results of the study show that the variable Capital Adequacy Ratio (CAR) has a positive but not significant effect on ROA. Operational Cost of Operational Income (BOPO) has a significant negative effect on ROA. Loan to Deposit Ratio (LDR) has no significant negative effect on ROA. Third Party Funds (DPK) have a significant positive effect on ROA. Whereas Non Performing Loans (NPL) have a significant positive effect on ROA. The coefficient of determination (adjusted R2) of 92.6% shows that the effect of Capital Adequacy Ratio, Operating Costs on Operating Income, Loan to Deposit Ratio, Third Party Funds and Non Performing Loans to profitability in banking companies is 92.6% while the rest is equal to 7.4% is explained by other factors outside the research model.Â Keywords: Return On Assets, Capital Adequacy Ratio, BOPO, Loan to Deposit Ratio, Third Party Funds and Non Performing Loans.